Antioxidative effect of soybean milk fermented by Lactobacillus plantarum Y16 on 2, 2 –azobis (2-methylpropionamidine) dihydrochloride (ABAP)-damaged HepG2 cells. (December 2021) - Wang, Arong; Hou, Kairong; Mu, Guangqing; Ma, Changlu; Tuo, Yanfeng
Abstract: In this study, the antioxidant capacity of the Lactobacillus plantarum Y16 fermented soybean milk was investigated by different chemical antioxidant methods and ABAP-induced oxidative stress model in HepG2 cells. It was found that the L. plantarum Y16 fermented soybean milk had better radical scavenging ability for hydroxyl and DPPH radicals, and had better ferric ion reduction ability compared with unfermented soybean milk. The cellular antioxidant assay (CAA) analysis revealed that the CAA values of ethanol and water extracts of L. plantarum Y16 fermented soymilk were dose dependent. The further research showed that the ethanol and water extracts of L. plantarum Y16 fermented soybean milk protected the HepG2 cells against ABAP oxidative damage through activating Nrf2/Keap1 signaling pathway and up-regulating the expression of heme oxygenase-1(HO-1), superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GSH-PX). The results showed that the antioxidant capacity of L. plantarum Y16 fermented soybean milk was superior to that of unfermented soybean milk.